Jews and gender : the challenge to hierarchy - Frankel, Jonathan 1935-2008 (Studies in contemporary Jewry, 2000)
This collection of articles is devoted to the theme of Jews and gender, including topics such as feminism in Judaism, Jewish women in history, gender and military service in Israel, and sociodemographic studies of Jewish women.